2007
DOI: 10.1111/j.1473-2165.2007.00295.x
|View full text |Cite
|
Sign up to set email alerts
|

Reduction in the appearance of facial hyperpigmentation by topical N‐acetyl glucosamine

Abstract: Glucosamine has been reported to inhibit melanin production in melanocyte culture. It thus has a potential to reduce hyperpigmentation via topical use. Due to stability limitations of glucosamine, we chose to clinically evaluate the stable derivative N-acetyl glucosamine (NAG). Based on in vitro Franz cell testing, NAG is a good skin penetrant. In an 8-week, double-blind, placebo-controlled, left-right randomized, split-face clinical test, topical 2% NAG reduced the appearance of facial hyperpigmentation. In a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
41
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(48 citation statements)
references
References 22 publications
6
41
0
1
Order By: Relevance
“…Multiple, double-blind, controlled, clinical trials demonstrated the clear benefit of 2% N-acetyl glucosamine in the treatment of hyperpigmentation secondary to sun exposure [28,30] but none secondary to inflammatory causes.…”
Section: N-acetyl Glucosaminementioning
confidence: 99%
“…Multiple, double-blind, controlled, clinical trials demonstrated the clear benefit of 2% N-acetyl glucosamine in the treatment of hyperpigmentation secondary to sun exposure [28,30] but none secondary to inflammatory causes.…”
Section: N-acetyl Glucosaminementioning
confidence: 99%
“…N-acetyl glucosamine (NAG), which is an amino sugar that occurs widely in nature and essential component of dermal tissues, is well-known for its role as a precursor of hyaluronic acid, a key structural composition of skin. NAG shown to inhibit melanin production in melanocyte culture, thus has a potential to reduce hyperpigmentation by topical administration (Bissett et al, 2007). To improve NAG penetration into the skin Shatalebi et al encapsulated it into niosomes and investigated its flux across excised rat skin using Franz diffusion cells.…”
Section: Whitening Effectmentioning
confidence: 99%
“…It reduces melanin production and downregulates the gene expression of several intracellular cytoskeletal proteins that are involved in melanosome transport within the cell. In a double-blind, placebocontrolled split face study, 2% NAG proved effective (30). Although formulating a topical agent has been difficult due to its instability, a recent study has demonstrated the potential for niosomes for improved NAG localization to the skin [30,31].…”
Section: Newer Topical Bleaching Formulationsmentioning
confidence: 99%